Taking into account the wider evolutionary context of cumulative cultural evolution - Claidière, Nicolas (The Behavioral and brain sciences, 2020)
The target article reviews evidence showing that technological reasoning is crucial to cumulative technological culture but it fails to discuss the implications for the emergence of cumulative cultural evolution (CCE) in general. The target article supports the social view of CCE against the more ecological alternative and suggests that CCE appears when specialised individual-learning mechanisms evolve.